Marine Polysaccharides Advances and Multifaceted Applications - Ahmed, Shakeel; Soundararajan, Aisverya (Pan Stanford Publishing, an imprint of Pan Stanford, 2018)
In the past few decades, marine organisms, including macroalgae and microalgae, have been extensively explored as potential sources of bioactive compounds with applications in various fields such as pharmaceuticals, biomedicine, cosmetics and foodstuffs. Marine polysaccharides, such as chitin/chitosan, ulvans, fucans, alginates and carrageenans, are biochemical compounds with several important properties such as anticoagulant and/or antithrombotic, immunomodulatory, antitumor, antilipidemic, hypoglycemic, antibiotic, anti-inflammatory and antioxidant properties. Due to their biocompatible, nontoxic and biodegradable nature, marine polysaccharides offer a better alternative to be used in advancement of the biomedical field. This book focuses on marine polysaccharides; their derivatives, blends, composites and hydrogels; and their multifaceted applications in various fields. The book also discusses the various aspects of marine polysaccharides from the point of view of chemistry and related applications. It is an important reference for marine biotechnologists, natural product scientists, students, researchers and academicians working in the area of materials science, marine science and polymer chemistry
Keywords: SCIENCE / Life Sciences / Biology / Marine Biology; TECHNOLOGY & ENGINEERING / Material Science; Microbial polysaccharides / Industrial applications; Marine organisms; Bioactive compounds